2010
DOI: 10.1007/s12161-010-9139-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Pink-Flesh Guava (Psidium guajava L.): Effect of Extraction Techniques and Solvents

Abstract: The effect of commonly used techniques and solvents in the antioxidant activities of pink-flesh guava fruit were studied. The extraction techniques compared were homogenization, shaking, sonication, magnetic stirring, and maceration for 1, 2, and 3 days. The solvent systems used were methanol, ethanol, and acetone at three different concentrations (50%, 70%, and 100%) and with 100% distilled water. The antioxidant activity of the fruit was evaluated using Folin-Ciocalteu index, ferric-reducing antioxidant powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 28 publications
4
150
1
3
Order By: Relevance
“…The dried guava powder showed good retention of antioxidants when compared with soluble extract through DPPH activity, which confirms that spray drying process does not affect the antioxidant capacity of the fruit powder. Earlier studies on the antioxidant activity of Guava through different extraction procedures found aqueous extraction through simple aqueous homogenization was best procedure [28]. This comparative study between guava powder and guava soluble extract showed higher quality of guava powder was maintained after processing.…”
Section: Antioxidant Activitymentioning
confidence: 62%
“…The dried guava powder showed good retention of antioxidants when compared with soluble extract through DPPH activity, which confirms that spray drying process does not affect the antioxidant capacity of the fruit powder. Earlier studies on the antioxidant activity of Guava through different extraction procedures found aqueous extraction through simple aqueous homogenization was best procedure [28]. This comparative study between guava powder and guava soluble extract showed higher quality of guava powder was maintained after processing.…”
Section: Antioxidant Activitymentioning
confidence: 62%
“…In contrast, those genotypes that showed the greatest AA for the four stages evaluated were P4, P6 and P7 and were indicated as being the most promising. The different values observed for antioxidant activity are due to the intrinsic characteristics of the fruit, to the method used for obtaining the extract, the extraction solution, the method of determination, and the compounds with an antioxidant action present in the tested material (MUSA et al, 2011). Genovese et al (2008) reported a capacity of 4.4 g mol -1 for guava of the species P. guineensis, of 1.8 g mol -1 in the araçá boi (Eugenia stipitata), of 141.0 g mol -1 in camu-camu and of 9.0 g mol -1 in cambuci.…”
Section: Resultsmentioning
confidence: 99%
“…The determination of antioxidant activity through TPC was carried out according to the method of [10]. About 100 μL papaya extracts was added with 0.4 mL distilled water and 0.5 mL diluted Folin-Ciocalteu reagent.…”
Section: Total Phenol Content (Tpc)mentioning
confidence: 99%
“…The determination of antioxidant activity through FRAP was carried out according to the method of Musa et al [10]. FRAP reagent was prepared fresh as using 300 mM acetatebuffer, pH3.6 (3.1 g sodium acetate trihydrate, plus 16 mL glacial acid made up to 1:1 with distilled water); 10 mM TPTZ (2,4,6-tris (2-pyridyl)-s-triazine), in 40 mMHCLl; and 20 mM FeCl3•6H2O in the ratio of 10:1:1 to give the working reagent.…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 99%
See 1 more Smart Citation